First report of solitary cavitation nodules in the lungs with Mycobacterium canariasense - Liu, Jing; Wu, Meiying; Zhang, Jianping; Shi, Cuilin (The Journal of Infection in Developing Countries, 2024)
Introduction: Mycobacterium canariasense is a relatively rare and rapidly growing nontuberculous mycobacterium (NTM) infection. Case report: This case report describes a 36-year-old man with a Canariasense infection in the lung with solitary cavitation nodules located subpleural on CT scan, for which the final diagnosis was made by metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF-mNGS). It was successfully treated with levofloxacin and amikacin. Conclusions: This experience is instructive because clinical diagnostic and CT imaging characteristics and treatment strategy guidelines for pulmonary infections caused by M. canariasense have not yet been established.